Privilege in Migration: The Benefits of Nationality for Northern Migrants in the Middle East - Chaveneau, Clio (2022)
The term “expatriation”, contested but frequently used, encompasses the idea that Westerners are not “average” migrants, if not at all migrants and it contributes to dismiss discussions on their privileges. Some researchers have been working on revealing the racial and class privileges and how it affects the migratory experiences of the so-called “expats”. In this chapter, I examine the roles that the nationality plays in the migratory experience and the living conditions of Northern migrants residing in a specific region, the Middle East. Based on extensive fieldworks I conducted in the Occupied Palestinian Territories (2012–2015) and in the United Arab Emirates (2017–2020), I will highlight how privileges shape western migration in the Middle East. The OPT and the UAE, although presenting different economic and social contexts, offer interesting illustrations of the way Westerners are benefiting from their passport to migrate as well as the cultural and symbolic capital attached to their nationalities: languages, education, professional experiences, and cultural imaginaries can be mobilized by individuals to find interesting job opportunities. In this chapter, focusing on two types of privileges - the freedom of movement and the access and position in the local job market – I argue that nationality plays a crucial role in both, the conditions of migration as well as the relationships with both the locals and the others (underprivileged) migrants.